Effect of Foot-and-Mouth Disease Vaccine on Pregnancy Failure in Beef Cows - Garcia-Pintos, Camila; Riet-Correa, Franklin; Menchaca, Alejo (Frontiers in Veterinary Science, 2021)
Abstract This study evaluates whether the foot-and-mouth disease (FMD) vaccination increases pregnancy failures in Bos taurus beef cows. A total of 3,379 cows were assigned to two experimental groups to receive (n=1,722) or not receive (n=1,657) a FMD vaccine (commercial preparation containing FMD virus, O1 Campos and A24 Cruzeiro) at different gestational age. Pregnancy diagnosis was performed by ultrasonography at vaccination time (Day 0), and the cows were classified by days of pregnancy as follows: a) less than 29 days after mating (presumed pregnant cows, n=778), b) between 30 and 44 days of pregnancy (n=1,100), c) 45 and 59 days of pregnancy (n=553), and d) between 60 and 90 days of pregnancy (n=948). Pregnancy failure was determined 30 days after vaccination by a second ultrasound examination. Cows that were vaccinated within 29 days after mating had a 7.8% greater failed pregnancy rate than non-vaccinated cows (44.1%, 163/370 vs. 36.3%, 148/408, respectively; P<0.05). Cows vaccinated between 30 and 44 days of gestation had a pregnancy failure rate greater than non-vaccinated cows (4.9%, 28/576 vs. 2.5%, 13/524, respectively; P<0.05). When cows received the vaccine between days 45 and 90 of gestation no differences in pregnancy failure were observed (0.8%, 6/776 vs. 1.2%, 9/725, respectively; P=NS). Body temperature and local adverse reactions to vaccine inoculation were recorded in a subset of 152 multiparous cows. Hyperthermia (>39.5°C) was detected on Day 1 or 2 in 28.0% (21/75) of vaccinated vs. 7.8% (6/77) of non-vaccinated cows (P<0.01). Local adverse reaction to the FMD vaccine inoculation increased from 0.0% (0/75) on Day 0, to 15.7% (11/75) on Day 4, and 38.7% (29/75) on Day 10 (P<0.01). On Day 30 local reaction was detected in 10.5% (34/323) and fell to 2.2% on Day 60 (7/323) post vaccination (P<0.01). In conclusion, FMD vaccine increases pregnancy failure when it is administered before 45 days of gestation, an effect that was associated with hyperthermia and local adverse reaction. No effect on pregnancy failure was found when vaccination was performed after 45 days of gestation.